(3JMa GdYQhV aj dWa GdYQhVs - (3GdMSjfj, GdSHRhGQj, GdfGFjfj, HgGA GdOjf, eMeO Hf eMeO HGbQs ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg Pj GdWhd GdWhjd(B... (3CeG HYO agPg JMa YQhV aj dWa GdYQhV MhJ efgG GdhGLH GdeaQhV de MGhd HMQ GdTYQ Cf jNhV(B...s
(3BNQgG (B:s
(3aEf GNJdaJG egYfi agh ef HOjY GdLfGS jJfGaS ajg GdfGS(B... (3jLYdgeG eNJdajf hRfG aj bUjOI (B... (3JeJ GdQSGdI GdehSheI(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B630s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdYQhV hGdbhGajs